Urinary minerals excretion among primary schoolchildren in Dubai—United Arab Emirates - Rola Al Ghali; Carla El-Mallah; Omar Obeid; Ola El-Saleh; Linda Smail; Dalia Haroun (PLoS ONE, 2021)
Introduction Urinary excretion of calcium (Ca), magnesium (Mg), phosphorus (P), iodine and fluoride is used to assess their statuses and/or the existence of metabolic abnormalities. In the United Arab Emirates (UAE), the urinary concentration of these minerals among children have not been documented. Materials and methods A cross-sectional study, including 593 subjects (232 boys and 361 girls), was conducted among healthy 6 to 11-year-old Emirati children living in Dubai. Non-fasting morning urine samples and anthropometrical measurements were collected and analyzed. Results were expressed as per mg of creatinine (Cr). Results On average, estimated Cr excretion was 17.88±3.12 mg/kg/d. Mean urinary Ca/Cr, Mg/Cr and P/Cr excretions were 0.08±0.07 mg/mg, 0.09±0.04 mg/mg, and 0.57±0.26 mg/mg respectively. Urinary excretion of Ca, Mg and P were found to decrease as age increased. Urinary excretion and predicted intake of fluoride were lower than 0.05 mg/kg body weight per day. Surprisingly, more than 50% of the children were found to have urinary iodine excretion level above adequate. Conclusion The Emirati schoolchildren had comparable levels of urinary Ca, Mg and P excretion to other countries. The 95% percentile allows the use of the current data as a reference value for the detection of mineral abnormalities. Fluoride excretion implies that Emirati children are at low risk of fluorosis. The level of urinary iodine excretion is slightly higher than recommended and requires close monitoring of the process of salt iodization to avoid the harmful impact of iodine overconsumption.